Are Myriophyllum alterniflorum biomarker responses to arsenic stress differentially affected by hydrodynamic conditions?. (June 2019) - Krayem, Maha; Deluchat, Véronique; Hourdin, Philippe; Labrousse, Pascal
Abstract: Arsenic (As) is a significant contaminant in the environment and its detection through macrophytes can provide a powerful tool. Myriophyllum alterniflorum constitutes a good candidate by virtue of its ability to accumulate contaminants, and moreover its biomarkers can respond to the presence of trace metals and metalloids. The objective of this study therefore is to evaluate the watermilfoil response to As exposure under several hydrodynamic conditions since it is well known that hydrodynamics affect plant functioning. For this purpose, fresh watermilfoil plants are subjected to three hydrodynamic conditions, namely laminar, turbulent and calm, in a synthetic medium either enriched or not by 100 μg.L −1 arsenic for 21 days. Growth, pigment content (chlorophyll a, b and carotenoids), respiratory and photosynthetic activities, osmotic potential and hydrogen peroxide concentration are all monitored. Arsenic accumulation is measured separately in the roots and shoots of Myriophyllum alterniflorum . On the one hand, it should be noted that arsenic induces: (i) a significant increase in H2 O2 content; (ii) a decrease in osmotic potential, pigment content, photosynthesis and respiration rates, shoot and root growth; and (iii) an inhibition of shoot branching. Moreover, a higher accumulation of this metalloid in roots than in shoots, regardless of the hydrodynamic condition, is witnessed. While on the other hand, hydrodynamic conditions only affect watermilfoil morphology and arsenic accumulation. Also, the younger and older parts have experienced differential toxic effects. Overall, our results suggest the effective use of M. alterniflorum in both water quality biomonitoring and phytoremediation studies. Highlights: Arsenic exposure induces responses of biomarkers. Arsenic impacts the biochemical, physiological, and morphological biomarkers. Hydrodynamic conditions affected watermilfoil morphology and arsenic accumulation. Older parts of the shoot show more toxic effects than the younger ones at the tip.